Evaluating Smart Mobile Public Services for Bridging Digital Divide in Rural Governance Systems - Muhtarom, Muhtarom; Desrianti, Dewi Immaniar; Sukendri, Nengah; Green, Thomas; Kamil, Muhammad Farhan (Pandawan Sejahtera Indonesia, 2026)
The persistent digital divide remains a critical challenge for rural governance, particularly in developing regions where disparities in infrastructure, digital literacy, and institutional capacity hinder equitable access to public services. This study aims to evaluate the impact of mobile-based public services on improving governance outcomes, specifically in terms of accessibility, efficiency, transparency, citizen participation, and public trust within rural contexts. A quantitative research design is employed using Structural Equation Modeling (SEM), based on survey data collected from 250 rural respondents and supported by national digital access indicators to ensure empirical robustness. The results reveal that mobile-based public services significantly enhance governance performance, with strong positive effects on accessibility (β= 0.72), efficiency (β = 0.68), and transparency (β = 0.70). These improvements subsequently foster higher levels of citizen participation (β = 0.75), which plays a critical mediating role in strengthening public trust (β = 0.80). Additionally, the measurement and structural models demonstrate strong reliability, convergent validity, discriminant validity, and overall model fit, confirming the robustness of the proposed framework. This study contributes to the digital governance literature by offering an integrated socio-technical and empirical SEM-based framework that explains how mobile-based services can effectively bridge the digital divide and enhance rural governance outcomes. Furthermore, it provides practical and policy-relevant insights aligned with Sustainable Development Goals (SDG 9, SDG 10, and SDG 16), supporting inclusive and sustainable digital transformation strategies.